Impact of injector tip deposits on gasoline direct injection engine combustion, fuel economy and emissions. (15th March 2020) - Zhang, Wenbin; Zhang, Zhou; Ma, Xiao; Awad, Omar I.; Li, Yanfei; Shuai, Shijin; Xu, Hongming
Graphical abstract: Highlights: Injectors were fouled for continuous 55 h using market fuel without detergent. Pulse width, flow loss and SEM images were used to identify injector coking status. Effects of injector deposits on engine combustion and emissions were investigated. Indicated thermal efficiency improved by up to 0.44% after removing tip deposits. Particulate emissions were reduced by up to 45% when tip deposits were removed. Abstract: Gasoline direct injection (GDI) engine development is facing the great challenges in both fuel economy and particulate emissions. Trade-off is often required in GDI engines to sacrifice fuel economy in order to meet the strict emission regulations. GDI injector deposits have been identified as a potential cause of increased particulate emissions. In this work, a series of experimental tests was conducted on a 1.5 L turbocharged GDI engine to further understand the effect of injector deposits. The deposits formed on the injector tip surface were removed after the 55-hour fouling test and their effects on fuel consumption, in-cylinder combustion, thermal efficiency and engine out emissions were investigated before and after the removal. The spray characteristics of an identical injector under clean and fouled conditions were examined and the deposits inside the injector nozzle holes were observed by a scanning electron microscope. The test injectors were mildly fouled with an average of 1.5% flow rate loss and 1.84% injection pulse width increase. After removing the injector tip surface deposits, the engine combustion phase became advanced and the peak in-cylinder pressure increased. The combustion efficiency was close to 98% and showed no significant change. Although the indicated thermal efficiency was only slightly improved by 0.31–0.44% after removing the tip surface deposits, the particulate emissions were significantly affected and reduced by up to around 45%. At the meantime, NOx emissions moderately increased by approximately 12% after removal and no significant change occurred in the THC and CO emissions.